2013
DOI: 10.1002/cssc.201300004
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Dehydration of Carbohydrates on In Situ Exfoliatable Layered Niobic Acid in an Aqueous System under Microwave Irradiation

Abstract: A simple and efficient microwave-assisted HNb(3)O(8) catalytic process is proposed for the dehydration of carbohydrates in the aqueous phase. A 5-hydroxymethylfurfural (HMF) yield of 55.9 % was achieved at a high substrate/catalyst weight ratio of 50 from a 10 wt % fructose solution, which is close to the yield achieved by homogeneous aqueous systems. The critical factor for this performance is the fast in situ exfoliation of layered HNb(3)O(8) with the aid of microwave irradiation, which leads to quasi-homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Instead, the process times to achieve the respective furfural yield are presented. The studies mentioned herein are only limited to cases in which homogeneous catalysis is employed, although there is a number of studies that compare microwave and conventional heating in the presence of heterogeneous catalysts as well . The effect of microwave heating in such heterogeneous systems is beyond the scope of this work.…”
Section: Appendixmentioning
confidence: 99%
“…Instead, the process times to achieve the respective furfural yield are presented. The studies mentioned herein are only limited to cases in which homogeneous catalysis is employed, although there is a number of studies that compare microwave and conventional heating in the presence of heterogeneous catalysts as well . The effect of microwave heating in such heterogeneous systems is beyond the scope of this work.…”
Section: Appendixmentioning
confidence: 99%
“…The use of ILs in carbohydrate transformations was first suggested by Liu et al in 2005 [126]. recycle because of coke deposition; however, it can be fully recovered by calcination at 400 °C for 2 h. In addition, the fructose dehydration reaction was catalyzed by HNb 3 O 8 in water [93]. 55.9% HMF yield was achieved possibly due to the fast in situ exfoliation of layered HNb 3 O 8 with the aid of microwave irradiation, which leads to quasihomogeneous catalytic behavior.…”
Section: Ilsmentioning
confidence: 99%
“…The 31 P MAS NMR measurements using TMPO as a probe molecule indicated that the acid strength of transition metal oxide nanosheet aggregates dramatically depends on the constituent element compositions, in the order of HTiNbO5 < HNb3O8 < HNbWO6 < HTaWO6 ( Figure 10) [26]. These nanosheet aggregates have so far been applied for hydrolysis of disaccharides [13], furfural formation from xylose [29] and HMF formation from fructose and glucose [30,31]. HTiNbO 5 nanosheets had a high surface areas of ca.…”
Section: Metal Oxide Nanosheet Aggregatesmentioning
confidence: 99%
“…These nanosheet aggregates have so far been applied for hydrolysis of disaccharides [13], furfural formation from xylose [29] and HMF formation from fructose and glucose [30,31]. HTiNbO5 nanosheets had a high surface areas of ca.…”
Section: Metal Oxide Nanosheet Aggregatesmentioning
confidence: 99%